النشاط السياسي والعسكري للمهاجرين الجزائريين في فيدرالية جبهة ،التحرير الوطني بفرنسا من خلال نماذج: أحمد دوم، عمر بوداود، عبد الحفيظ شروك (1955-1962) - بسمة فرحي (جامعة البليدة2- كلية العلوم الإنسانية والإجتماعية, 2025)
يعتبر موضوع المهاجرين الجزائريين الى فرنسا من أهم المواضيع التي تستحق الدراسة والبحث، وذلك للدور الذي لعبته هذه الفئة في دعم الثورة التحريرية ماديا ومع نويا، فالتطرق لنضال هذه الفئة ينا جعل نلمس جانبا مهم ا من تاريخ الجزائ ر لمعاصر ، الذي لا يزال يحتاج إلى بحث للوصول إلى الحقيقة التاريخية، و ،لإبراز الدور الذي لعبته جاليتنا بفرنسا، ومن أجل ذلك وقع الاختيار على بضعة نماذج متمثلة في )أحمد دوم ،عمر بوداود، عبد الحفيظ شروك( لدراسة نشاطها السياسي و العسكري بفيدر الية جبهة التحرير الوطني بفرنسا ،)بين تحديدا سنتي 4555)تأسيس فيدرالية الجبهة بفرنسا( و 4562)فتعبر عن سنة استقلال الجزائر بالاعتماد على المنهج الوصفي و المنهج التحليلي، المناسبين للدراسة، مع الاستعانة ب مجمو عة م ن المصادر والمراجع المساعدة؛ كالوثائق الأرشيفية، والشهادات الحية والمذكرات الشخصية بالإضافة الى الكتب الخادمة للموضوع. و في الختام تخلص الدراسة الى أهم النتائج التي تبين الدور الذي لعبت ه كل شخصي ة وانعكاسات ،ذلك على الفيدرالية ونشاطها؛ فأحمد دوم كان من الأو ائل الذين أسسوا لتنظيم فيدرالية جبهة التحرير الوطني رغم كل العوائق والعراقيل التي صادفتهم. أما عمر بوداود فقد نجح في تحقيق أهدافه المسطرة و هي: التحكم في أوضاع المهاجرين الجزائريين بفرنسا، تعزيز مالية جبهة التحرير الوطني، نقل الكفاح المسلح إلى أراضي الخصم. وبالنسبة لشروك عبد الحفيظ لقد كان له الفضل الكبير للتعريف بالقضية الوطنية من خلال عملية .محاولة اغتيال وزير الإعلام الفرنسي "جاك سوستال" ، التي قام بها مع رفاقه The subject of Algerian immigrants in France is among the most significant topics deserving study and research due to the crucial role this group played in materially and morally supporting the liberation revolution. Examining the struggle of this group allows us to touch upon an important aspect of contemporary Algerian history, which still requires research to uncover historical truth and highlight the role played by our community in France. To this end, the choice fell on a few models represented by (Ahmed Doum, Omar Boudaoud, Abdelhafid Cherrouk) to study their political and military activities within the framework of the National Liberation Front (FLN) in France, specifically between the years (1955, the establishment of the FLN federation in France) and (1962, the year of Algeria's independence), relying on the descriptive and analytical methods suitable for the study, along with the help of a set of assisting sources and references; such as archival documents, live testimonies, personal memoirs, and books serving the subject. In conclusion, the study arrives at the most important results demonstrating the role played by each individual and its impact on the federation and its activities: Ahmed Doum was one of the first to organize the establishment of the FLN federation despite all obstacles and hurdles they faced. Omar Boudaoud succeeded in achieving his outlined objectives, which were controlling the situation of Algerian immigrants in France, strengthening the finances of the FLN, and transferring the armed struggle to enemy territory. As for Abdelhafid Cherrouk, he had a significant role in raising awareness about the national cause through the assassination attempt on French Minister of Information "Jacques Soustelle" carried out by him and his comrades.
(1962 -1871)المهاجرون المغاربة بفرنسا ودورهم الوطني والقومي
Keywords: جبهة التحرير الوطني; المهاجرين الجزائريين; فيدرالية جبهة التحرير الوطني; نشاط السياسي للمهاجرين الجزائريين